No wrong decisions in an all‐wrong situation. A qualitative study on the lived experiences of families of children with diffuse intrinsic pontine glioma. Issue 9 (2nd June 2022) - De Clercq, Eva; Grotzer, Michael; Landolt, Markus A.; von Helversen, Bettina; Flury, Maria; Rössler, Jochen; Kurzo, Andrea; Streuli, Jürg
Abstract: Background: Diffuse intrinsic pontine glioma (DIPG) is a rare, but lethal pediatric brain tumor with a median survival of less than 1 year. Existing treatment may prolong life and control symptoms, but may cause toxicity and side effects. In order to improve child‐ and family‐centered care, we aimed to better understand the treatment decision‐making experiences of parents, as studies on this topic are currently lacking. Procedure: The data for this study came from 24 semistructured interviews with parents whose children were diagnosed with DIPG in two children's hospitals in Switzerland and died between 2000 and 2016. Analysis of the dataset was done using reflexive thematic analysis. Results: For most parents, the decision for or against treatment was relatively straightforward given the fatality of the tumor and the absence of treatment protocols. Most of them had no regrets about their decision for or against treatment. The most distressing factor for them was observing their child's gradual loss of independence and informing them about the inescapability of death. To counter this powerlessness, many parents opted for complementary or alternative medicine in order to "do something." Many parents reported psychological problems in the aftermath of their child's death and coping strategies between mothers and fathers often differed. Conclusion: The challenges of DIPG are unique and explain why parental and shared decision‐making is different in DIPG compared to other cancer diagnoses. Considering that treatment decisions shape parents' grief trajectory, clinicians should reassure parents by framing treatment decisions in terms of family's deeply held values and goals.